2017
DOI: 10.4314/gjds.v14i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Towards Creating Sustainable Ecotourism Interventions: Practical Lessons from Mesomagoro, Ghana

Abstract: Ecotourism has, over the past three decades, been employed globally as a tool to secure a balance between the need for environmental preservation and the sustenance of the communities which depend directly on it. Consequently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In some instances, little attention is given within government for its coordination. The increasing trend as from 2011 to 2021 is an indication of the paradigm shift regarding (eco)tourism governance in SSA (Backman and Munanura 2015, Mbaiwa 2015, Boakye 2017). The trend is also a reflection of adherence and consistency towards the 'White paper' of tourism approved by the UNWTO General Assembly in 2011, which states that (eco)tourism governance, in the case of national as well as local destinations, is worthy of special attention (Duran 2013).…”
Section: Evolution In Ecotourism Governance Studies In Sub-saharan Af...mentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, little attention is given within government for its coordination. The increasing trend as from 2011 to 2021 is an indication of the paradigm shift regarding (eco)tourism governance in SSA (Backman and Munanura 2015, Mbaiwa 2015, Boakye 2017). The trend is also a reflection of adherence and consistency towards the 'White paper' of tourism approved by the UNWTO General Assembly in 2011, which states that (eco)tourism governance, in the case of national as well as local destinations, is worthy of special attention (Duran 2013).…”
Section: Evolution In Ecotourism Governance Studies In Sub-saharan Af...mentioning
confidence: 99%
“…All the studies on conflict management within the West African sub-region also considered conflict management strategies to be less effective and recommended the need for conflicts in ecotourism to be appropriately handled if ecotourism must attain its objectives (Asuk and Nchor 2018). Although many studies in the different sub-regions of SSA consider transparency to be weak (Pasape et al 2015, Agyeman et al 2019, Forje et al 2020a), Boakye (2017), observed that improved transparency in the practice of ecotourism (from decision making process through implementation and clear benefit sharing) in the Mesomagoro in the eastern peripheries of the Kakum National Park in Ghana had encouraged all actors and the local communities to be engaged in the development of ecotourism in the area. In West Africa, the cases that treated accountability observed that poor accountability was affecting ecotourism, with focus mainly on tourism in protected areas.…”
Section: Governance Principles Researched On Within the Ecotourism Se...mentioning
confidence: 99%